IDENTIFIKASI DAN MOLECULAR DOCKING KOMPONEN UTAMA MINYAK KULIT BUAH JERUK NIPIS SEBAGAI AGEN ANTIKANKER - Indah Hairunisa; Normaidah Normaidah; Sylvan Septian Ressandy; Fhirda Azhari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Cancer is the highest cause of death in the world. This disease is known to have different regulations from other diseases. The development of drugs today is to target anticancer drugs on cancer regulation sites at Hallmark of Cancer. Lime (Citrus aurantifolia) is one type of Citrus (orange) which contains beneficial chemical compounds and active as anticancer agents. Lime peel is known to have bioactive content in the form of essential oils and flavonoids such as hesperidin and hesperitin. The content of this compound is closely related to anticancer activity. This study aims to identify the content of compounds in lime peel oil and the study of molecular docking silico in these compounds in protein that play a role in the regulation of cancer cells. Lime peel oil is obtained using the steam distillation method then analyzed using GC-MS to determine its constituent components to be analyzed in silico then using YASARA 10.1.8, MarvinSketch 15.4.20, and PLANTS software. The results showed that the main components of lime peel oil were d-limonen and beta-pinen with a percentage of 59.71% and 36.81%. In silico analysis shows that each of these compounds has an affinity greater than the native ligand on caspase-8 proteins (protein regulation of apoptosis). Based on these results it can be concluded, that the lime peel oil has the potential to be developed as an anticancer agent.